Communication Literacy Education: Effective Communication Patterns in the Elderly - Ismaya Ismaya; Andi Ahmad Chabir GalibAndi Ahmad Chabir; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
Communicating means humans are trying to achieve common meaning and humans are trying to share information, ideas, or attitudes with other participants. If there is no similarity of meaning between the communicator and the communicant, that is, the communicant does not understand the message he receives, then communication does not occur or is not communicative. Communication is one aspect that is always needed by every human being. This proves that communicating is important in every stage of life. Communication is also needed by elderly parents or the elderly. Their need to communicate to others can also be distinguished between each other. This research uses a qualitative method because the source of the data is not a human being but a document. This research 'includes a type of library research', while the data collection uses documentation techniques. The 'data analysis used is content analysis. The results showed that the elderly person (elderly) is someone whose approach differs between one elderly person and another elderly person, so that in communicating with them also requires different communication patterns in order for similar meanings to occur so as to create effective communication.